Targeting homologous recombination using imatinib results in enhanced tumor cell chemosensitivity and radiosensitivity. - Choudhury, A; Zhao, H; Jalali, F; Al Rashid, S; Ran, J; Supiot, S; Kiltie, A; Bristow, R (2009)
RAD51 is a key protein in the homologous recombination (HR) pathway of DNA double-strand break repair, and HR represents a novel target for cancer therapy. Because imatinib (Gleevec) has been reported to reduce RAD51 protein levels, we tested the clonogenic survival for RT112, H1299, PANC1, and PC3 tumor cell lines of varying p53 status and normal GM05757 normal fibroblasts after exposure to single agent imatinib (0-20 micromol/L; 0-72 hours). We also combined imatinib with DNA damaging agents that are toxic to RAD51-deficient cells, including ionizing radiation, gemcitabine, and mitomycin C. We observed decreased nuclear expression and chromatin binding of RAD51 protein following imatinib treatment. Imatinib also resulted in decreased error-free HR as determined by a flow cytometry-based integrated direct repeat-green fusion protein reporter system; this correlated to reduced RAD51 expression. Clonogenic survival experiments revealed increased cell kill for imatinib-treated cells in combination with ionizing radiation, gemcitabine, and mitomycin C, due in part to mitotic catastrophe. In experiments using imatinib and gemcitabine, tumor cell lines were sensitized to a greater extent than normal fibroblasts. This preservation of the therapeutic ratio was confirmed in vivo using PC3 xenograft growth delay and intestinal crypt cell clonogenic assays. HR inhibition may be an additional mechanism of action for the chemosensitization and radiosensitization of solid tumors with imatinib with preservation of the therapeutic ratio.